Cytotoxic effect of aeglemarmelos (l.) Leaves in Hep g2 cell lines- an invitro study - K.J.UMA DEVI; V.VANITHA (International Journal of Pharma and Bio Sciences, 2016)
Aegle marmelos, is a medicinal plant from India, used for treating cancer-related symptoms in the Indian system of medicine. Its leaf, root, bark, seed and fruits are valued highly as Ayurvedic medicine. In the present study, the active fraction of Aegle marmelos was found to induce apoptosis in Hep G2 cells through NFκB deactivation followed by activation of proapoptotic factor p53. To evaluate this apoptotic induction, the mRNA levels of NFκB were determined using semiquantitative RT– PCR assay. NFκB levels were significantly down-regulated in HepG2 cells following the treatment with active fraction. Similarly, incubation of HepG2 cells with active fraction resulted in increased expression of p53 mRNA levels. The activation of NFκB appears to be a very strong antiapoptotic signal which inhibits TNF α mediated apoptosis pathway. Semiquantitative RT –PCR assay in treated HepG2 cells depicted decreased levels of NFκB which reflects activation of apoptosis through TNFα mediated pathway. Increased levels of p53 mRNA reflects activation of transcription factor p53 which inturn activates Bax proteins and various other transcription factors finally leading to intrinsic apoptotic pathway. These pathways converge to a final common pathway involving the activation of caspases that cleave regulatory and structural molecules and culminate in the death of the cell. Mechanism of apoptotic induction was further evaluated through elevated levels of caspases 3 and 9 enzymes. Thusthe ability of the Aegle marmelos to induce apoptosis by a multi prolonged cascade of events suggests that it might be an ideal therapeutic for solid tumors of liver.